Islamic Perspective for Sustainable Financial System - Sarac, Mehmet; Hassan, Mohammed Kabir (Istanbul University Press, 2020)
The real world free-market economies have long been driven by the linear economy paradigm in which the ecological environment is not recognized as a resource. The linear process, a natural consequence of capitalism, has caused the fast exhaustion of the resources for the sake of "development." After serious environmental catastrophes and financial crises, the common sense of the world has admitted that there problems with conventional economics and has begun to search for more 'sustainable' economic and financial systems. The idea that firms should operate in a manner where they provide dignified living to people and consider the needs of next generations has become widespread especially in last three decades. Termed as the 'stakeholder approach', this understanding contributed to pave the way to the notion of 'sustainability', which calls for taking measures to solve the fundamental problems such as income and wealth inequality, poverty, corruption, climate change and disappearance of animal species. As a result of the global concern around the effect of human actions on our environment, the idea of sustainability received serious attention and was given a fillip by the publications by The United Nations, which outlined the famous Sustainable Development Goals (SDGs). This call is addressed not only to the real sector, but to the finance sector that provide funds required to operate the real economic activities. As a result of increasing consciousness of sustainability and public pressure, the finance sector has also begun to consider the social and environmental concerns more seriously. Banks, in addition to reporting their own compliance with sustainability, have also begun reporting the compliance with sustainability of the corporations and industries that they fund. Contrary to capitalist or socialist understanding and practice, Islamic economics is already guided by the motivation of comprehensive development and its preservation in a 'universal and sustainable manner' as manifested in the objectives of the Islamic Law (Maqasid'ul-Shariah). Islamic economics is based on the 'circular manner' which prevents the exhaustion of the resources and environmental disasters. Three prominent examples of the characeristics of Islamic economics that distinguish it from the capitalist understanding relates to the concepts of private ownership, consumption and charity. Islamic law does recognize private ownership rights, yet this right is not absolute. While the unique creator Allah (swt) has absolute ownership, human beings, as the vicegerents of Allah in this world, possess the wealth as His trustee. The custodial characteristic of the ownership concept burdens strict responsibilities on human beings. Islam clearly bans wasting and orders the efficient use of resources. In a true Islamic economy the resources and wealth are equitably distributed and charity mechanism functions well. Lending is considered as a means of charity, rather than a business to make money. In sum, the development goal in Islamic economics is strictly characterized by its universality and sustainability. The governments in Muslim countries and all firms that are known for their observance of Islamic values are expected to truly adopt and practice the concept of sustainability. Islamic financial institutions play a key role in achieving a sustainable economy. If they observe the compliance, not only with Islamic rules in their own products and services but also with the sustainability principles in the operations of their customers that they fund, the sustainability in the entire economy would be secured. The firms that want to work with the Islamic financial industry would be constrained to observe the sustainability in their operations, along with the complying with the Shariah criteria and the financial ratios.viii The aim of this book is to elaborate the concept of sustainability from the perspective of Islamic economics and finance. It basically presents how the sustainability, which has recently been considered important by the developed non-Muslim world, is already an embedded phenomenon in Islamic economics and finance. The initial articles present the embeddedness of the concept of sustainable development within Islamic economics and finance. Then, the following articles point out more specific dimensions and implementations in selected countries. We hope that the governments in Muslim countries and managements of those financial and non-financial firms, known for their observance of Islamic principles will truly adopt the SDGs that will lead towards the circular economy paradigm and the entire world would notice the pioneer role of principles of Islamic finance in achieving these goals.